Pengaruh jenis persalinan terhadap risiko depresi postpartum pada ibu nifas - Ririn Ariyanti; Detty Siti Nurdiati; Dhesi Ari Astuti (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2016)
Abstract: This study aims to determine the effect of type of delivery onthe risk of postpartum depression in mothers postpartum in hospitalsSleman. This type of research is analytic survey with a retrospective cohortdesign. Hospital research sites in Sleman, Yogyakarta. The population inthis study are all postpartum mothers who visited the poly obstetrics andgynecology in the months from October to December 2015. The totalsample of 110, the data analysis performed univariate and bivariate withchi-square test. The results showed the incidence of the risk of postpartumdepression in mothers postpartum in hospitals sleman was 36.3%, type oflabor significantly influence the risk of postpartum depression with thevalue (OR = 3.716, 95% CI 1.620 to 8.522).